Smart Medical Devices: Integrating AI, Sensor Technology, and Bioengineering for Next-Generation Healthcare Solutions - Hammadi, Jamil Mahmoud Jamil; Jari, Sajjad Obaid An’ad; Asr, Hussein Riad Hussein (American Journal of Botany and Bioengineering, 2025)
Technological breakthroughs in sensor technology, artificial intelligence (AI), wireless communication, bioengineering, and data analysis contribute to the advancement of portable smart devices with affordable prices. The frequent use of smart devices improves the quality of life in healthcare, urban diagnosis, environmental monitoring, and many other fields. Smart health monitoring systems collect biological signals from the human body using smart medical devices. One of the most remarkable attributes of wearable and implantable medical devices is the capability to track the health condition regardless of the location of the patients and caregivers through wireless communication . Analysis of the data from medical devices has elevated the diagnostic capability from the expert knowledge of human physicians to an objective analysis of number crunchers. Hence, understanding data analytics and AI techniques applied to medical devices is a move towards the future of smart devices in the healthcare industry. An increase in the aging population accelerates the demand for affordable remote health monitoring. Sensor technology is an essential part of wearables to monitor vital signs. Wireless and connected monitoring devices are made portable and battery operated that lay a foundation for telemonitoring. The shift of patient care from main healthcare premises to home or community expands the early-stage recognition of diseases. The advance of human movement recognition methods reduces the complication of evaluating the physical quality of the elderly. The development of imagers, biomicrofluidics, sensors, actuators, and procedures in bioengineering enables smart wearables. Smartphone-based health devices connected over the internet of things improve the diagnosis and treatment efficiency of coronary heart disease patients and diabetes patients. Wearable medical devices integrated with sensors, actuators, thermal switches, records, and communication modules toward the measurement of 10 biological signals at home and evaluation of arrhythmias and diabetes events in hospitals are developed to reduce healthcare expenditure through automatic patient care.